2017
DOI: 10.3892/mmr.2017.7519
|View full text |Cite
|
Sign up to set email alerts
|

Panax Notoginseng Saponins attenuates sevoflurane-induced nerve cell injury by modulating AKT signaling pathway

Abstract: General anesthesia in patients with or at risk for neuronal injury remains challenging due to the neurotoxic effects of volatile anesthetics. One inhalation anesthetic, sevoflurane, induces neuronal damage, including neuroapoptosis, and learning and memory impairment. Panax Notoginseng Saponins (PNS) is the active ingredient of Sanqui and has been reported to exert neuroprotective effects. In the current study, the protective effect of PNS on sevoflurane‑induced nerve cell injury was explored. Cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…As a critical anti-apoptosis factor, Bcl-2 inhibits apoptosis predominantly by inhibiting caspase pathway. On the other hand, Bax conjugates with Bcl-2, forming heterodimer, to induce the release of cytochrome c, activate caspase pathway and promote apoptosis (32,33). Caspases are a family of cysteine-aspartic proteases.…”
Section: Discussionmentioning
confidence: 99%
“…As a critical anti-apoptosis factor, Bcl-2 inhibits apoptosis predominantly by inhibiting caspase pathway. On the other hand, Bax conjugates with Bcl-2, forming heterodimer, to induce the release of cytochrome c, activate caspase pathway and promote apoptosis (32,33). Caspases are a family of cysteine-aspartic proteases.…”
Section: Discussionmentioning
confidence: 99%
“…These have been used for more than a thousand years with generally carry a low risk of negative side effects. Panax notoginseng (Burk) F. H. Chen , as traditional Chinese medicine has a long history of high clinical value, such as anti-inflammatory [ 16 , 20 , 31 , 32 ], anti-oxidation, inhibition of platelet aggregation, regulation of blood glucose [ 27 , 33 , 34 ] and blood pressure [ 35 , 36 , 37 ], inhibition of neuronal apoptosis [ 14 , 38 , 39 ], and neuronal protection. Currently, Panax notoginseng (Burk) F. H. Chen may improve mental function, have anti-insomnia and anti-depression effects, alleviate anxiety, and decrease neural network excitation [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are others reported to be flavonoids, cyclopeptides, saccharides, and inorganic elements [ 30 ]. Pharmacological studies have shown that notoginseng and its extracts have many functions, such as anti-inflammatory [ 16 , 20 , 31 , 32 ], anti-oxidation, inhibition of platelet aggregation, regulation of blood glucose [ 27 , 33 , 34 ] and blood pressure [ 35 , 36 , 37 ], inhibition of neuronal apoptosis [ 14 , 38 , 39 ], and neuronal protection [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…These have been used for more than a thousand years with generally carry a low risk of negative side effects. Panax notoginseng, as traditional Chinese medicine has a long history of high clinical value, such as anti-inflammatory [16,20,31,32], antioxidation, inhibition of platelet aggregation, regulation of blood glucose [27,33,34] and blood pressure [35][36][37], inhibition of neuronal apoptosis [14,38,39] and neuronal protection. Currently, Panax notoginseng may improve mental function, have anti-insomnia and anti-depression effects, alleviate anxiety, and decrease neural network excitation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…And there are others reported to be flavonoids, cyclopeptides, saccharides and inorganic elements [30]. Pharmacological studies have shown that notoginseng and its extracts have many functions, such as anti-inflammatory [16,20,31,32], anti-oxidation, inhibition of platelet aggregation, regulation of blood glucose [27,33,34], blood pressure [35][36][37], inhibition of neuronal apoptosis [14,38,39] and neuronal protection [30].…”
Section: Introductionmentioning
confidence: 99%